OXIDANT-ANTIOXIDANT BALANCE CHANGES IN ADIPOSE TISSUES OF HIGH FAT DIETINDUCED OBESE RATS: DEPOT-SPECIFIC MANNER AND INEFFECTIVENESS OF NACETYLCYSTEINE - Kahraman, Cemil; Alver, Ahmet; Bodur, Akın; İnce, İmran; Altay, Diler Us; Canpolat, Sinan (My University, 2019)
Objective: The aims of study were to investigate effects of both N-acetylcysteine (NAC, an antioxidant) and high fat diet (HFD) to oxidative stressin differently located adipose tissues and the liver.Methods: Our study is created from control, HFD and NAC groups (n=6). Control group was fed with only standard diet. HFD group was fed withonly HFD. NAC group was fed with HFD, and additionally that group received NAC (2 g/L). All groups were fed with designated diets for 85 days.Antioxidant enzyme activities, glutathione, and malondialdehyde were measured in epididymal, perirenal, subcutaneous adipose tissues, and liver.Results: In the HFD group, malondialdehyde (MDA) levels increased in perirenal adipose tissue and liver. In addition, superoxide dismutase (SOD)and catalase activities in the HFD group were lower both epididymal and perirenal adipose tissue, whereas glutathione peroxidase activities werelower in subcutaneous and epididymal adipose tissue. Glutathione was lower in liver tissue alone. In subcutan adipose tissue, the glutathione andSOD activities increased due to NAC administration.Conclusion: The present findings showed that oxidative stress and antioxidant enzyme profiles were variable in localized adipose tissue in differentregions. Thought antioxidant enzyme activities in some tissues increased due to NAC application, these increases were insignificant in terms of oxidant-antioxidant balance.
Keywords: Biyoloji; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp